Determining organic versus conventional food emissions to foster the transition to sustainable food systems and diets: Insights from a systematic review. (20th December 2022) - Chiriacò, Maria Vincenza; Castaldi, Simona; Valentini, Riccardo
Abstract: The global food system is a major contributor to climate change with 23–42% of total greenhouse gas (GHG) emissions. Thus, the transition to sustainable food systems and dietary patterns represents a big challenge and a key solution to feed a fast-growing world population while maintaining safe planet boundaries of sustainability. Organic farming is often proposed as a sustainable option, however a debate is open on its effectiveness in reducing the impact on climate when compared to conventional agriculture. Therefore, there is a need for clear indicators of climate and environmental sustainability to duly inform the food system actors and foster an effective transition towards sustainable food production and consumption. The carbon footprint (CF) is one of the most used indicators to assess the sustainability of food as it measures the contribution to climate change in terms of GHG emissions with different metrics (e.g. GHG per unit of product or per unit of land). Through a systematic analysis of the existing peer-reviewed studies allowing an unbiased comparison of product-based vs land-based CF, this study shows that organic food has on average lower impact on climate than conventional, both when the CF is assessed per 'land unit' (−43% GHG emissions, average) and per 'product unit' (−12% GHG emissions, average). However, the two CF metrics provide diverse results, even opposite in some cases, when individual conventional vs organic food types are compared: organic food results to be more sustainable than conventional in almost all cases when the 'land unit' CF metric is compared; conversely, conventional food results to be less impacting than organic in the 29% of cases when the 'product unit' CF is considered. According to these results, although the CF per unit of product is far more used and provides useful indications on the food emissions intensity, in some cases it can bring a misleading message towards unsustainability, with the paradox of making more preferable food that apparently shows lower impact per unit of product while having higher emissions per land unit. Contrariwise, the CF per unit of land better reflects the actual agricultural contribution to climate change which is driven by the land-atmosphere GHG fluxes. According to this study's results and in view of the global climate policies' targets which foster organic food production and the transition to sustainable diets, an extensive conversion of the existing global croplands into organic lands would significantly contribute to reducing total GHG emissions from the land sector.